Slave Revolt on Screen: the Haitian Revolution in Film and Video Games - Sepinwall, Alyssa Goldstein (University Press of Mississippi, 2021)
In Slave Revolt on Screen: The Haitian Revolution in Film and Video Games author Alyssa Goldstein Sepinwall analyzes how films and video games from around the world have depicted slave revolt, focusing on the Haitian Revolution (1791–1804). This event, the first successful revolution by enslaved people in modern history, sent shock waves throughout the Atlantic World. Regardless of its historical significance however, this revolution has become less well-known—and appears less often on screen—than most other revolutions; its story, involving enslaved Africans liberating themselves through violence, does not match the suffering-slaves-waiting-for-a-white-hero genre that pervades Hollywood treatments of Black history. Despite Hollywood’s near-silence on this event, some films on the Revolution do exist—from directors in Haiti, the US, France, and elsewhere. Slave Revolt on Screen offers the first-ever comprehensive analysis of Haitian Revolution cinema, including completed films and planned projects that were never made. In addition to studying cinema, this book also breaks ground in examining video games, a pop-culture form long neglected by historians. Sepinwall scrutinizes video game depictions of Haitian slave revolt that appear in games like the Assassin’s Creed series that have reached millions more players than comparable films. In analyzing films and games on the revolution, Slave Revolt on Screen calls attention to the ways that economic legacies of slavery and colonialism warp pop-culture portrayals of the past and leave audiences with distorted understandings.
Section: vi, 339 pages : illustrations ; 24 cm.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À nettoyer; _À vérifier-Cinéma

El color de la razón: racismo epistemológico y razón imperial - Castro-Gómez, Santiago; Eze, Emmanuel Chukwudi; Henry, Paget (Ediciones del Signo, 2014)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Introduction de feminismos desde abya yala - Gargallo, Francesca (Revue d'Études Décoloniales, 2020)
Quand les conditions requises pour le dialogue ne sont pas réunies, il est difficile d’expliquer à une femme blanche : " écoute, nous ne voulons pas qu’on nous impose des de critères féministes hégémoniques " . Cela étant, je reconnais et j’apprécie tout ce que j’ai appris sur les différents courants féministes. Car grâce à eux, je me reconnais comme sujette épistémique et je peux me penser à partir du corps et de l’espace où je vis. Ou encore tisser des idées féministes. C’est ainsi que la construction consciente de mon identité féministe communautaire se renforce et en même temps, nous contribuons au mouvement féministe dans le monde. Par exemple, l’une des étapes que nous devons franchir passe par la langue : nommer dans nos propres langues, qui auront été libérées, les catégories et les concepts que nous élaborons pour analyser l’oppression subie par notre peuple dans l’histoire et notre libération en tant que femmes indigènes, autochtones, paysannes, rurales, ou villageoises. Francesca Gargallo est une écrivaine et féministe autonome italo-mexicaine. Licenciée en philosophie de la Sapienza de Rome et docteure en Études Latinoaméricaines de l’UNAM mexicaine, cette spécialiste de l’histoire des idées féministes, prenant acte de l’échec de l’utopie socialiste, propose de chercher des alternatives à partir d’un féminisme clairement antiraciste, qui fasse la critique de l’ eurocentrisme. Elle s’intéresse au concept de colonialisme interne de Pablo González Casanova, ou de Silvia Rivera Cusicanqui. Le livre dont nous traduisons deux extraits, Feminismos desde Abya Yala. Ideas y proposiciones de las mujeres de 607 pueblos en NuestraAmérica, a été publié en 2012 aux éditions Desde abajo.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

Ensayos de crítica feminista en nuestra América - Mendoza, Breny (Editorial Herder, 2019)
El feminismo hegemónico latinoamericano entró en crisis en los años noventa por su creciente contubernio con el Estado liberal, así como por su práctica política carente de teoría. No supo cómo responder a los desaires de la izquierda masculinista y quedó intacto por los nuevos teóricos de la descolonialidad. Su acción y pensamiento no sólo se manifestaron profundamente colonizados por Occidente, sino que no encontraron una voz clara para entrar en diálogo con ciertas corrientes del feminimo latinoamericano que cuestionaron sus postulados de género, raza y heteronormatividad.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Feminismos disidentes en América Latina y el Caribe // Féminismes dissidents en Amérique latine et aux Caraïbes - Curiel, Ochy; Falquet, Jules; Masson, Sabine (Editions Antipodes, 2005)
La idea de elaborar un número sobre las luchas de las mujeres y las feministas en América Latina y el Caribe surgió de un encuentro entre Sabine Masson (Suiza), Jules Falquet (Francia) y Ochy Curiel (República Dominicana), cuyos caminos se cruzaron en el continente latinoamericano por razones personales y políticas. Debatimos y reflexionamos juntas sobre la cuestión de las barreras de "raza" y de clase que nos atraviesan a las feministas de diferentes partes del mundo, y que son en particular el reflejo de las relaciones de dominación entre el Sur y el Norte. Precisamente por estas barreras, las experiencias políticas y el trabajo de construcción colectiva de muchas feministas y mujeres, especialmente de América Latina y el Caribe, siguen siendo desconocidas para la mayoría de las feministas de otras latitudes, y de poco interés para las revistas académicas feministas de los países ricos. Oponerse a esta invisibilización y contribuir, aunque sea a nivel experimental y muy modesto, a la deconstrucción de estas barreras, fue nuestra principal motivación para organizar este número en una revista francófona como Nouvelles Questions Féministes. Sin embargo, el trabajo de coordinación presentó importantes contradicciones: primero, entre nosotros mismos. En primer lugar, tuvimos que reconocer e integrar las diferencias y similitudes de nuestras respectivas posiciones, para llegar a un consenso que nos permitiera desarrollar esta cuestión juntos. En segundo lugar, nos enfrentamos al riesgo de reproducir una vez más el saqueo de los conocimientos de las mujeres indias, afrodescendientes y mestizas latinoamericanas y caribeñas por parte de los "expertos del Norte". Los textos se traducirían al francés, lo que significaría que una ínfima minoría de mujeres latinoamericanas y caribeñas tendría acceso a ellos, mientras circulaban por Europa, enriqueciendo una vez más el conocimiento de las mujeres de los países ricos con el trabajo, las luchas, las historias y los escritos de las mujeres de los países pobres. Ante este problema, decidimos que la publicación de este número fuera acompañada de una versión en español, con el objetivo de hacer circular y compartir esta producción intelectual en América Latina y el Caribe L’idée de faire un numéro sur les luttes de femmes et les luttes féministes en Amérique latine et aux Caraïbes a surgi de la rencontre entre Sabine Masson (Suisse), Jules Falquet (France) et Ochy Curiel (République Dominicaine), dont les chemins se sont croisés sur le continent latino-américain pour des raisons personnelles autant que politiques. Nous avons débattu et réfléchi ensemble sur la question des barrières de « race » et de classe qui nous traversent, nous les féministes de différentes parties du monde, et qui sont notamment le reflet des rapports de domination entre le Sud et le Nord. Justement à cause de ces barrières, les expériences politiques et le travail de construction collective de beaucoup de féministes et de femmes, notamment latino-américaines et des Caraïbes, demeurent inconnus de la plupart des féministes d’autres latitudes, et intéressent peu les revues féministes académiques des pays riches. S’opposer à cette invisibilisation et contribuer, même si ce n’est qu’à un niveau expérimental et très modeste, à déconstruire ces barrières, a constitué notre principale motivation pour organiser ce numéro dans une revue francophone comme Nouvelles Questions Féministes . Néanmoins, le travail de coordination présentait d’importantes contradictions : d’abord, entre nous. Pour commencer, nous avons dû reconnaître et intégrer les différences et les similitudes de nos positions respectives, afin de parvenir à un consensus qui nous permette d’élaborer ce numéro ensemble. Ensuite, nous nous confrontions au risque de reproduire encore une fois le pillage des connaissances des femmes indiennes, afro-descendantes et métisses latino-américaines et des Caraïbes par les « expertes du Nord ». Les textes allaient être traduits en français, c’est-à-dire qu’une infime minorité de femmes latino-américaines et des Caraïbes pourrait y avoir accès, pendant qu’ils circuleraient en Europe, enrichissant une fois de plus le savoir des femmes des pays riches à partir du travail, des luttes, des histoires et des écrits des femmes des pays pauvres. Face à ce problème, nous avons décidé que la publication de ce numéro allait s’accompagner d’une version en espagnol, dans le but de faire circuler et de partager cette production intellectuelle en Amérique latine et aux Caraïbes
Link Catalogue Open WorldCat http://www.worldcat.org/oclc/728004883
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Visual Disobedience: The Geopolitics of Experimental Art in Central America, 1990-Present - Cornejo, Kency (N.D., 2014)
This dissertation centers on the relationship between art and politics in postwar Central America as materialized in the specific issues of racial and gendered violence that derive from the region's geopolitical location and history. It argues that the decade of the 1990s marks a moment of change in the region's cultural infrastructure, both institutionally and conceptually, in which artists seek a new visual language of experimental art practices to articulate and conceptualize a critical understanding of place, experience and knowledge. It posits that visual and conceptual manifestations of violence in Central American performance, conceptual art and installation extend beyond a critique of the state, and beyond the scope of political parties in perpetuating violent circumstances in these countries. It argues that instead artists use experimental practices in art to locate manifestations of racial violence in an historical system of domination and as a legacy of colonialism still witnessed, lived, and learned by multiple subjectivities in the region. In this postwar period artists move beyond the cold-war rhetoric of the previous decades and instead root the current social and political injustices in what Aníbal Quijano calls the `coloniality of power.' Through an engagement of decolonial methodologies, this dissertation challenges the label "political art" in Central America and offers what I call "visual disobedience" as a response to the coloniality of seeing. I posit that visual colonization is yet another aspect of the coloniality of power and indispensable to projects of decolonization. It offers an analysis of various works to show how visual disobedience responds specifically to racial and gender violence and the equally violent colonization of visuality in Mesoamerica. Such geopolitical critiques through art unmask themes specific to life and identity in contemporary Central America, from indigenous genocide, femicide, transnational gangs, to mass imprisonments and a new wave of social cleansing. I propose that Central American artists–beyond an anti-colonial stance–are engaging in visual disobedience so as to construct decolonial epistemologies in art, through art, and as art as decolonial gestures for healing.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Imágenes de lo extraordinario. Memorias de un continente poblado por monstruos. - Gil, Slenka Leandra Botello; Camacho, Daianna Sierra (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
Este trabajo presenta los resultados de la investigación Imágenes de lo extraordinario: monstruos americanos del siglo XVI, proceso de creación artística desarrollado por los estudiantes del Semillero de Investigación en Artes Visuales (SINAV) del programa de Artes Visuales de la Universidad Nacional Abierta y a Distancia (UNAD) entre 2018 y 2019. Para analizar de manera crítica e histórica la construcción de identidades sobre lo latinoamericano, se tomó como marco de análisis la representación de lo monstruoso en los relatos y las imágenes construidas por los cronistas de Indias en el siglo XVI, los cuales marcaron procesos de marginalización cultural, construcción de subjetividades y dinámicas de poder, y presentaron al habitante americano como una otredad que estaba fuera de los límites de la cultura dominante occidental. Se presentan los postulados teóricos sobre lo monstruoso como marco para el análisis histórico y la creación de obra, con una metodología de trabajo colaborativo y en gran parte virtual. Posteriormente, se exponen algunos resultados de la investigación histórica que dan paso a detallar el proceso de creación de obra que culminó con la exposición de la instalación audiovisual Imágenes de lo extraordinario, así como con una amplia serie de ilustraciones contemporáneas sobre lo monstruoso y un producto digital en formato página web donde se presenta una cartografía de lo monstruoso en América Latina y se recogen las memorias de todo el proyecto. This work presents the results of the research Images of the Extraordinary: American Monsters of the 16th Century, artistic creation process developed by the students of the Research Seedbed in Visual Arts (SINAV, for its initials in Spanish) of the Visual Arts program of Universidad Nacional Abierta y a Distancia (UNAD) between 2018 and 2019. With the objective of analyzing, in a critical and historical way, the construction of identities on Latin American matters, the representation of the monstrous in the stories and images constructed by the chroniclers of the Indies in the 16th century was used as a framework of analysis. These chroniclers marked processes of cultural marginalization, construction of subjectivities and power dynamics, and presented the American inhabitant as an otherness that was outside the limits of the dominant Western culture. The theoretical postulates about the monstrous are presented as a framework for historical analysis and the creation of works, with a collaborative and largely virtual working methodology. Some results of the historical research are then presented, which gives way to detailing the process of creating work that culminated in the exhibition of the audiovisual installation Images of the Extraordinary, as well as a wide range of contemporary illustrations on the monstrous and a digital product in web page format where a cartography of the monstrous in Latin America is presented and the memories of the whole project are collected.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Genealogías críticas de la colonialidad en América Latina, África, Oriente - Segato, [et al.], Rita Laura (Universidad Nacional de San Martín, 2016)
El espesor de este libro es propio de este tiempo. Cuerpos que se desplazan en masivas inmigraciones huyendo de todo tipo de violencias alcanzan a más de sesenta millones de personas, la mayor cifra de refugiados desde la segunda guerra mundial. El mundo experimenta una crisis humanitaria sobrecogedora ante la cual las potencias apelan a los mismos discursos que ya Aimé Césaire o Fanon condenaran. Dramatismo del exilio de este nomadismo a escala planetaria, al cual Stuart Hall calificaría como “amensia imperial”. Genealogías críticas de la colonialidad en América Latina, África, Oriente es un libro que deja al descubierto la piel del mundo contemporáneo. Un hecho cultural disruptivo que, anudado a una genealogía latinoamericana abierta a sí misma y hacia Otros Sures se interroga sobre los intrincados modos de narrar y silenciar los pasados coloniales.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Revista N'oj Panel on Decolonizing Aesthetics - Latinx Research Center (2020)
The Latinx Research Center's Revista N'oj hosted a round table discussion on Decolonial Aesthetics titled, "Decolonizing Art & Praxis in the Time of Covid-19." The talk included Jesus Barraza, Dr. Guisela Latorre, Dr. Mauricio Barros de Castro, and Dr. Laura E. Pérez. The panel was moderated by Revista N'oj editor, Abraham Ramirez.
Revista N'oj : Issue No.2 (2020) Event was sponsored by the Latinx Research Center at the University of California, Berkeley
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Coloniality at Large: Latin America and the Postcolonial Debate - Moraña, Mabel; Dussel, Enrique; Jáuregui, Carlos A. (Duke University Press, 2008)
Postcolonial theory has developed mainly in the U.S. academy, and it has focused chiefly on nineteenth-century and twentieth-century colonization and decolonization processes in Asia, Africa, the Middle East, and the Caribbean. Colonialism in Latin America originated centuries earlier, in the transoceanic adventures from which European modernity itself was born. Coloniality at Large brings together classic and new reflections on the theoretical implications of colonialism in Latin America. By pointing out its particular characteristics, the contributors highlight some of the philosophical and ideological blind spots of contemporary postcolonial theory as they offer a thorough analysis of that theory’s applicability to Latin America’s past and present. Written by internationally renowned scholars based in Latin America, the United States, and Europe, the essays reflect multiple disciplinary and ideological perspectives. Some are translated into English for the first time. The collection includes theoretical reflections, literary criticism, and historical and ethnographic case studies focused on Ecuador, Guatemala, Mexico, Brazil, the Andes, and the Caribbean. Contributors examine the relation of Marxist thought, dependency theory, and liberation theology to Latin Americans’ experience of and resistance to coloniality, and they emphasize the critique of Occidentalism and modernity as central to any understanding of the colonial project. Analyzing the many ways that Latin Americans have resisted imperialism and sought emancipation and sovereignty over several centuries, they delve into topics including violence, identity, otherness, memory, heterogeneity, and language. Contributors also explore Latin American intellectuals’ ambivalence about, or objections to, the “post” in postcolonial; to many, globalization and neoliberalism are the contemporary guises of colonialism in Latin America. Contributors : Arturo Arias, Gordon Brotherston, Santiago Castro-Gómez, Sara Castro-Klaren, Amaryll Chanady, Fernando Coronil, Román de la Campa, Enrique Dussel, Ramón Grosfoguel, Russell G. Hamilton, Peter Hulme, Carlos A. Jáuregui, Michael Löwy, Nelson Maldonado-Torres, José Antonio Mazzotti, Eduardo Mendieta, Walter D. Mignolo, Mario Roberto Morales, Mabel Moraña, Mary Louise Pratt, Aníbal Quijano, José Rabasa, Elzbieta Sklodowska, Catherine E. Walsh
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); _Nettoyé

Close Encounters: The Next 500 Years - Farrell Racette, Sherry. (Plug In Editions., 2011)
Catalogue d'exposition publié à l'occasion de l'exposition tenue au Plug In Institute of Contemporary Art, Urban Shaman Contemporary Aboriginal Art, et Winnipeg Art Gallery, du 22 janvier au 8 mai 2011. Now is the moment to reconfigure our notions of time to reveal alternative ways of thinking and being for the future. In Close Encounters: The Next 500 Years Indigenous artists imagine the future within the context of present experiences and past histories. By radically reconsidering encounter narratives between native and non-native people, Indigenous prophecies, possible utopias and apocalypses, this exhibition proposes intriguing possibilities for the next 500 years. "We all in different measure have carved out the future," observes Hopi photographer and filmmaker, Victor Masayesva, in his book Husk of Time. "We are all clairvoyants, soothsayers, prophets, knowingly assuming our predictions. Close Encounters brings together over 30 Indigenous artists from across Canada, the United States, South America, Europe, Australia and New Zealand, including newly commissioned work from Rebecca Belmore, Faye HeavyShield, Kent Monkman, and Edward Poitras. Jimmie Durham's sculptural work A Pole to Mark the Centre of the World (at Winnipeg) will be an ongoing critique of widely held ideas surrounding space and location, while James Luna's poignant installation The Spirits of Virtue and Evil Await my Ascension, addresses issues of ritual and the passing of time. Close Encounters showcases artists and artworks that collectively invent provocative futures from a diversity of perspectives and practices. With its myriad histories, trajectories, tensions, collisions, and self-image(s), the city of Winnipeg offers an intriguing juxtaposition for these artistic mediations. Close Encounters: The Next 500 Years presents international Indigenous perspectives in a city that in many ways also epitomizes the future of Aboriginal people in Canada. Works in multiple venues throughout the city will serve as catalysts to invent different ways of thinking, acting, and being in the world of our shared future. At this pivotal moment in time, Close Encounters invites engagement with the speculative, the prophetic, and the unknown
Section: 1 volume (217 pages) : illustrations en coul. ; 26 cm.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé